Television pyrometry improvement - Markin, Maxim (Technology audit and production reserves, 2014)
The article analyzes the problem of television pyrometry improvement by determination of the range of linearity of the television system luminous-signal characteristics. The contemporary scientific literature practically does not have any materials on the relevant research methods or their results. It places special emphasis on the importance of the problems, laid down in this article. If we consider characteristics, that determine accuracy of the temperature measurement in methods of the television bispectral pyrometry, the main characteristics shall be equivalent wavelength, effective to the noise difference of color temperatures and luminoussignal characteristic. Clearly, accuracy of the temperature measurement is affected by a dark signal range of the specific device. First of all, in such a case it is necessary to make experimental studies of performance of the facilities, which are used today or evaluated from the perspective of their use in the bispectral television pyrometry. We have accumulated a considerable amount of experimental materials in course of the experiments. They concern formation of signals both in the television information-measuring system parameters of zonal melting, and in the television equipment of another destination, particularly, in the television pyrometers that can be used for control over the temperature conditions for pipe rolling technologies, in the television devices for food product quality control, environmental monitoring, in the television microscopy etc.